Antibacterial and cytotoxic efficacy of extracellular silver nanoparticles biofabricated from chromium reducing novel OS4 strain of Stenotrophomonas maltophilia. - Mohammad Oves (Public Library of Science (PLoS), 2013)
Biofabricated metal nanoparticles are generally biocompatible, inexpensive, and ecofriendly, therefore, are used preferably in industries, medical and material science research. Considering the importance of biofabricated materials, we isolated, characterized and identified a novel bacterial strain OS4 of Stenotrophomonas maltophilia (GenBank: JN247637.1). At neutral pH, this Gram negative bacterial strain significantly reduced hexavalent chromium, an important heavy metal contaminant found in the tannery effluents and minings. Subsequently, even at room temperature the supernatant of log phase grown culture of strain OS4 also reduced silver nitrate (AgNO3) to generate nanoparticles (AgNPs). These AgNPs were further characterized by UV-visible, Nanophox particle size analyzer, XRD, SEM and FTIR. As evident from the FTIR data, plausibly the protein components of supernatant caused the reduction of AgNO3. The cuboid and homogenous AgNPs showed a characteristic UV-visible peak at 428 nm with average size of ~93 nm. The XRD spectra exhibited the characteristic Bragg peaks of 111, 200, 220 and 311 facets of the face centred cubic symmetry of nanoparticles suggesting that these nanoparticles were crystalline in nature. From the nanoparticle release kinetics data, the rapid release of AgNPs was correlated with the particle size and increasing surface area of the nanoparticles. A highly significant antimicrobial activity against medically important bacteria by the biofabricated AgNPs was also revealed as decline in growth of Staphylococcus aureus (91%), Escherichia coli (69%) and Serratia marcescens (66%) substantially. Additionally, different cytotoxic assays showed no toxicity of AgNPs to liver function, RBCs, splenocytes and HeLa cells, hence these particles were safe to use. Therefore, this novel bacterial strain OS4 is likely to provide broad spectrum benefits for curing chromium polluted sites, for biofabrication of AgNPs and ultimately in the nanoparticle based drug formulation for the treatment of infectious diseases.